2008
DOI: 10.1099/mic.0.2007/014175-0
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulation of Hypocrea atroviridis growth occurs due to a cross-talk of carbon metabolism, blue light receptors and response to oxidative stress

Abstract: Light is a fundamental abiotic factor which stimulates growth and development of the majority of living organisms. In soil saprotrophic fungi, light is primarily known to influence morphogenesis, particularly sexual and asexual spore formation. Here we present a new function of light, the enhancement of mycelial growth. The photostimulated mycelial growth of the soil fungus Hypocrea atroviridis was detected on 17 (out of 95 tested carbon sources) carbohydrates and polyols, which are metabolically related to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 53 publications
(58 reference statements)
1
62
0
1
Order By: Relevance
“…3 (biochemical and physiological groups of carbon sources are given in Fig. 1A), PM analyses of different species displayed significant intraspecies diversities (H. jecorina) or were conserved (H. atroviridis) (Seidl et al, 2006;Friedl et al, 2008b). It was interesting to see that for H. jecorina the level of this variability was in the same range as that obtained by DNA-mediated transformation .…”
Section: Intra-and Inter-specific Variability In Carbon Source Utilizmentioning
confidence: 55%
See 4 more Smart Citations
“…3 (biochemical and physiological groups of carbon sources are given in Fig. 1A), PM analyses of different species displayed significant intraspecies diversities (H. jecorina) or were conserved (H. atroviridis) (Seidl et al, 2006;Friedl et al, 2008b). It was interesting to see that for H. jecorina the level of this variability was in the same range as that obtained by DNA-mediated transformation .…”
Section: Intra-and Inter-specific Variability In Carbon Source Utilizmentioning
confidence: 55%
“…Furthermore, Friedl et al (2008b) showed that enhancement of mycelia growth on various carbon sources is highly light-dependent. Carbon source utilization by PMs showed that Hypocrea atroviridis growth is light-stimulated on 17 of 95 carbon sources, which are mainly metabolically related to cellulose and hemicelluloses and can be found in the upper soil litter layer (Friedl et al, 2008b).…”
Section: Application Of Pms In Fungal Photobiologymentioning
confidence: 99%
See 3 more Smart Citations